2013
DOI: 10.1021/es3049459
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Enhanced Abiotic Iron Oxidation and the Effects of Chemical versus Biological Iron Cycling in Anoxic Environments

Abstract: This study introduces a newly isolated, genetically tractable bacterium (Pseudogulbenkiania sp. strain MAI-1) and explores the extent to which its nitrate-dependent iron-oxidation activity is directly biologically catalyzed. Specifically, we focused on the role of iron chelating ligands in promoting chemical oxidation of Fe(II) by nitrite under anoxic conditions. Strong organic ligands such as nitrilotriacetate and citrate can substantially enhance chemical oxidation of Fe(II) by nitrite at circumneutral pH. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
72
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 69 publications
5
72
0
Order By: Relevance
“…When nitrite diffuses through this EPS layer, green rust and goethite minerals form on the outside of the EPS layer, catalyzing Fe(II) oxidation and Fe(III) mineral formation (31,46,69). This mechanism would also explain the observations of (i) Fe(III) mineral formation without direct contact with the cells despite the low solubility of Fe(III) (14), (ii) oxidation of Fe(II) by sterile-filtered supernatants (67), and (iii) formation of an Fe(III) mineral coating on Shewanella putrefaciens cells incubated with Fe 2ϩ and NO 2 Ϫ (69). Is cell encrustation deleterious?…”
Section: Discussionmentioning
confidence: 94%
“…When nitrite diffuses through this EPS layer, green rust and goethite minerals form on the outside of the EPS layer, catalyzing Fe(II) oxidation and Fe(III) mineral formation (31,46,69). This mechanism would also explain the observations of (i) Fe(III) mineral formation without direct contact with the cells despite the low solubility of Fe(III) (14), (ii) oxidation of Fe(II) by sterile-filtered supernatants (67), and (iii) formation of an Fe(III) mineral coating on Shewanella putrefaciens cells incubated with Fe 2ϩ and NO 2 Ϫ (69). Is cell encrustation deleterious?…”
Section: Discussionmentioning
confidence: 94%
“…A more extensive treatment of the accelerating effect that metal ligands have on the rate of microbial Fe(II) oxidation was recently published (53), and the authors demonstrated that NO 2 Ϫ reacts more rapidly with Fe(II)-NTA than with unchelated Fe(II), suggesting another possible explanation for the high rate of Fe(II)-NTA oxidation by A. ebreus (Fig. 3b) (53). However, Fe(II)-NTA-agarose beads, which cannot penetrate the outer membrane, showed no oxidation by A. ebreus cell suspensions (Fig.…”
Section: Evidence Against An Inducible Fe(ii) Oxidoreductase Inmentioning
confidence: 99%
“…Some NDFO organisms, such as Pseudogulbenkiania ferrooxidans (67) or Pseudogulbenkiania sp. strain MAI-1 (53), release higher concentrations of extracellular NO 2 Ϫ during organotrophic nitrate reduction, which can react with extracellular Fe(II), especially in the presence of catalytic mineral phases, such as green rusts (21,48,49), or chelating ligands (53). However, NO should also be considered.…”
Section: Evidence Against An Inducible Fe(ii) Oxidoreductase Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the coatings occur on some silica grains, they are most common and best-developed on volcanic grains. Previous studies have identified anaerobic nitrate-dependent Fe(II)-oxidizing organisms capable of utilizing Fe(II) in mineral phases, including goethite, siderite, pyrite, neosilicates, and phyllosilicates (Chaudhuri et al, 2001;Weber et al, 2001;Shelobolina et al, 2003), although other studies have highlighted that Fe(II) oxidation can also occur abiotically by reacting with nitrite, a metabolic intermediate of denitrification (Cooper et al, 2003;Coby and Picardal, 2005;Pantke et al, 2011;Carlson et al, 2012;Picardal, 2012;Kopf et al, 2013).…”
Section: Carbonaceous Sedimentmentioning
confidence: 99%